Study on Ground Water Quality that Villagers Use in Their Daily Lives at Phonesim Village, Kaysone Phomvihan District, Savannakhet Province - Nanthalath, Phitsamone; vorayuth, Khongvilay; Naovongphachan, Kamkeo; Udon, Phetdara; Xayavong, Somsanouk (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purpose of this study was to investigate the quality of groundwater that is used in daily life in Phonesim village, Kaysone Phomvihan city, Savannakhet province. The study method was based on the primary data, such as the field sampling, with five water sampling points at the top, midpoint, southernmost, easternmost, westernmost, and 11 indicators to study water quality. Secondary or secondary information is studied from the relevant documents in the library, the Internet and other related organizations. The results of the study can be concluded that there are two indices with high values: FeacalColiform and Lead. For lead, the values ​​are as follows: the east point will be 0.09mg/L, the west point will be 0.1mg/L, the midpoint will be 0.11mg/L, the overhead point will be 0.11mg/L and the south point will be 0.12mg/L. Forbacteria, there is only one point above the standard: the midpoint, which has a value of 29mg/L. Foreach of the remaining indicators, it is considered to be within the standard range.